2017
DOI: 10.1111/nph.14687
|View full text |Cite
|
Sign up to set email alerts
|

The bias of a two‐dimensional view: comparing two‐dimensional and three‐dimensional mesophyll surface area estimates using noninvasive imaging

Abstract: Summary The mesophyll surface area exposed to intercellular air space per leaf area (Sm) is closely associated with CO2 diffusion and photosynthetic rates. Sm is typically estimated from two‐dimensional (2D) leaf sections and corrected for the three‐dimensional (3D) geometry of mesophyll cells, leading to potential differences between the estimated and actual cell surface area. Here, we examined how 2D methods used for estimating Sm compare with 3D values obtained from high‐resolution X‐ray microcomputed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 54 publications
0
77
1
Order By: Relevance
“…see Théroux-Rancourt et al, 2017), 350 this relationship could be used to estimate τ leaf based on 2D sections. Thus, τ leaf tends to 351 increase as porosity decreases, leading to a compounding effect on g IAS .…”
mentioning
confidence: 99%
“…see Théroux-Rancourt et al, 2017), 350 this relationship could be used to estimate τ leaf based on 2D sections. Thus, τ leaf tends to 351 increase as porosity decreases, leading to a compounding effect on g IAS .…”
mentioning
confidence: 99%
“…B). Although S c /S was determined using two‐dimensional leaf sections, Théroux‐Rancourt et al () showed that the curvature correction factor method (Thain ) we used is the easiest to apply and produces reliable estimates by comparing four two‐dimensional methods and a three‐dimensional method. Those indicated that S c /S, to some extent, regulated the variability of g m .…”
Section: Resultsmentioning
confidence: 99%
“…The mesophyll and chloroplast surface area exposed to leaf intercellular air spaces per leaf area (S m /S and/or S c /S) were calculated as in Evans et al () and Syvertsen et al (). Although we estimated all of the anatomical structures on the basis of two‐dimensional methods, the curvature correction factor method (Thain ) we used is the easiest to apply and produces reliable estimates compared with other two‐dimensional and three‐dimensional methods (Théroux‐Rancourt et al ). According to the suggestion of Théroux‐Rancourt et al (), we measured curvature correction factors for each tissue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…My favourite recent paper is Théroux‐Rancourt et al . () because it is the first to reveal the leaf mesophyll anatomy we might have missed by looking at two‐dimensional cross‐sections. New techniques often open a path to new understanding.…”
Section: What Are Your Favourite New Phytologist Papers Of Recent Yeamentioning
confidence: 99%